(3EOGQI GdJShjb (B:s (3aj HjFI GdYhdeI hGdEfJQfJ (B/s - (3GdUMf, eMeO aQjOs; (3WGQb, Wgs ((3GdEScfOQjI(B: s (3efTCI GdeYGQa(B, s, 2005)
(3WHjYI OhQ GdJShjb aj GdefXeGJ GdMOjKI(B-(3GdJQcjR Ydi GdeSJgdc ceONd ddfLGM GdJShjbj(B-(3JMbjb QVG GdYejd ef NdGd GdbjeI hGdLhOI hGdQVG(B-(3OhQ GdJShjb aj GdJNWjW GdESJQGJjLj(B-(3GdCShGb(B-(3fXe GdeYdheGJ GdJShjbjI hHMhK GdJShjb(B-(3GdJShjb GdYGdej(B-(3GSJQGJjLjGJ GdeRjL GdJShjbj(B((3GdefJL,GdSYQ(B)-(3GSJQGJjLjGJ GdeRjL GdJShjbj(B((3GdecGf,GdJQhjL(B)-(3JShjb GdNOeGJ(B-(3GdJShjb HGdCfJQfJs
Keywords: (3EOGQI GdJShjbs; (3GdJShjbs; (3GdJShjb HGdCfJQfJs